IMPLEMENTATION Of The REQUIRED SOCIAL WELFARE SERVICES (PPKS) PROGRAM IN IMPROVING SOCIAL WELFARE IN UPTD LIPONSOS KEPUTIH CITY SURABAYA - Simanjuntak, Grace Yohana; Anugrah, Serly Dian; Latifah, Nike Nur; Syabella, Vivin Ary; Rahmadani, Anggie Novita; Anisykurlillah, Rosyidatuzzahro (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
A person in need of Social Welfare Services (PPKS) is someone who cannot carry out their social functions properly because they are experiencing disorders, so that their living needs are not met physically or spiritually. The large number of PMKS in the city of Surabaya has created discomfort among the community. This research is to describe and analyze the implementation of the PPKS Program in improving Social Welfare for homeless people and ODGJ at UPTD LIPONSOS Keputih, Surabaya City. The research method is a descriptive qualitative approach using literature study. The results and discussion are that the implementation of the PPKS Program at UPTD LIPONSOS Keputih, which is based on Perwali Number 118 of 2021, has not run optimally. This is due to the lack of patient support staff (HR) and the amount of budget to manage UPTD LIPONSOS Keputih. The number of staff is not proportional to the number of patients resulting in staff being overwhelmed. Apart from that, the insufficient budget means that the provision of facilities for patients is also inadequate. So, the factors that influence the implementation of the PPKS Program at UPTD LIPONSOS Keputih must be considered for the success of the implementation, especially the human resource and budget factors for managing UPTD LIPONSOS Keputih.